Conservação do germoplasma na qualidade física, química e fisiológica de sementes de gergelim - Alves, Lucas Matheus Carvalho Ribeiro (2025)
Sesame is a crop of high economic value, standing out for its importance at national and international levels. Considering its importance, it is necessary to preserve seeds of this species in Germplasm Banks, aiming at the conservation and development of new cultivars. This study aimed to evaluate the influence of storage time in a cold chamber on the physical, chemical, and physiological quality of seeds from accessions that make up the sesame germplasm bank. The study included 18 genotypes (CNPA 89.35; BRA 4481; CNPA G4; ALCG; CNPA G2; SERIDÓ CHICO; SERIDÓ MONTEIRO; SERIDÓ D1; BRA27570; CNPA G18; APIG; AGSG; EPI-1A; AGS; SH63; SH13; SH13a; and SH30) preserved for different periods in the Active Germplasm Bank of Embrapa Cotton. The tests to determine physical, chemical, and physiological quality were conducted in controlled environments (BOD incubators), laboratories, and greenhouses, all belonging to Embrapa Cotton. The following parameters were evaluated: electrical conductivity, moisture content, weight of one thousand seeds, nutrient content, germination, germination speed index (IVG), vigor, seedling length, sand emergence, determination of dry mass, and emergence speed index (IVE). Significant differences were observed among genotypes, highlighting the importance of understanding how storage time at a temperature of 12 °C and 30% humidity may affect the physical, chemical, and physiological quality of sesame genotypes preserved in the Active Germplasm Bank. It was concluded that the conservation of sesame seeds under controlled conditions proved effective for maintaining physical, chemical, and physiological quality, although with distinct effects among the analyzed genotypes. While some genotypes maintained good physiological quality, others, particularly those stored for longer periods, showed signs of deterioration and reduced germination capacity. The genotypes BRA 27570, SH13, and SH13a stood out for their excellent physiological performance, with high germination rates, vigor, germination speed index, and emergence, even after prolonged storage periods. The preservation of sesame germplasm directly influences the emergence speed of some genotypes, regardless of the storage period, thereby highlighting the innate genetic factors at work.